2012
DOI: 10.1126/science.1223012
|View full text |Cite
|
Sign up to set email alerts
|

A Periciliary Brush Promotes the Lung Health by Separating the Mucus Layer from Airway Epithelia

Abstract: Mucus clearance is the primary defense mechanism that protects airways from inhaled infectious and toxic agents. In the current Gel-on-Liquid mucus clearance model mucus gel is propelled on top of a “watery” periciliary layer surrounding the cilia. However, this model fails to explain the formation of distinct mucus layer in health or why mucus clearance fails in disease. We propose a Gel-on-Brush model in which the periciliary layer is occupied by membrane spanning mucins and mucopolysaccharides densely tethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
857
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 713 publications
(879 citation statements)
references
References 61 publications
21
857
0
1
Order By: Relevance
“…Biophysical modeling predicts that clearance rates will not be affected by mucus layer heights as long as the mucus concentration remains between 2% and 5% solid content (20). However, clearance rates are impaired above 6% solids, and clearance ceases at concentrations above 8% solids, i.e., in severe cases of dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…Biophysical modeling predicts that clearance rates will not be affected by mucus layer heights as long as the mucus concentration remains between 2% and 5% solid content (20). However, clearance rates are impaired above 6% solids, and clearance ceases at concentrations above 8% solids, i.e., in severe cases of dehydration.…”
Section: Resultsmentioning
confidence: 99%
“…In the healthy airway, there is a thin coating of mucus that is continuously removed from the lung via the action of cilia, and if it accumulates by cough. This airway mucus is composed mainly of mucin glycoproteins and water, and provides a matrix for a wide variety of antimicrobial molecules including antibodies, defensins, protegrins, collectins, cathelicidins, lysozyme, histatins and nitric oxide21, 22, 23. When the mucus barrier has increased viscosity making it resistant to mucociliary clearance, or when the barrier is deficient or depleted, the risk of opportunistic microbial infection is increased 24.…”
Section: Introduction To Oxidative and Er Stressmentioning
confidence: 99%
“…Classically, the ASL was considered to consist of a mucus gel supported on a waterlike liquid layer surrounding cilia (gel-on-liquid model). More recently, Button and colleagues (52) showed that tethered mucins in the PCL form a mesh to prevent entry of gel-forming mucins and support ciliary beating, and they proposed a gel-onbrush model to describe the ASL. Photobleaching studies support this concept and have established that the fluid phase viscosity of the mucus layer and PCL are similar in non-CF subjects (7-10 times more viscous than saline), but significantly elevated in both regions in CF cultures (25)(26)(27)(28)(29)(30) times more viscous than saline) (51).…”
mentioning
confidence: 99%
“…Rehydration of the airway surface is thus considered to be a useful therapeutic approach in CF. Evidence from confocal microscopy, transmission electron microscopy, and fluorescence photobleaching indicate that the ASL consists of 2 discrete layers (51, 52): a superficial mucus layer that contains large gel-forming mucins (MUC5AC and MUC5B) that trap particulates for subsequent mucociliary clearance, and, in contact with cells and cilia, a periciliary layer (PCL) that contains large membranebound mucins (MUC1 and MUC4) (52). Classically, the ASL was considered to consist of a mucus gel supported on a waterlike liquid layer surrounding cilia (gel-on-liquid model).…”
mentioning
confidence: 99%
See 1 more Smart Citation